Electric double-layer capacitors with tea waste derived activated carbon electrodes and plastic crystal based flexible gel polymer electrolytes - Suleman, M; Deraman, M; Othman, MAR; Omar, R; Hashim, MA; Basri, NH; Nor, NSM; Dolah, BNM; Hanappi, MFYM; Hamdan, E; Sazali, NES; Tajuddin, NSM; et al. (IOP Publishing Ltd, 2024)
We report a novel configuration of symmetrical electric double-layer capacitors (EDLCs) comprising a plastic crystalline succinonitrile (SN) based flexible polymer gel electrolyte, incorporated with sodium trifluoromethane sulfonate (NaTf) immobilised in a host polymer poly (vinylidine fluoride-co-hexafluoropropylene) (PVdF-HFP). The cost-effective activated carbon powder possessing a specific surface area (SSA) of similar to 1700 m(2)g(-1) containing a large proportion of meso-porosity has been derived from tea waste to use as supercapacitor electrodes. The high ionic conductivity (similar to 3.6x10(-3) S cm(-1) at room temperature) and good electrochemical stability render the gel polymer electrolyte film a suitable candidate for the fabrication of EDLCs. The performance of the EDLCs has been tested by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and galvanostatic charge-discharge studies. The performance of the EDLC cell is found to be promising in terms of high values of specific capacitance (similar to 270 F g(-1)), specific energy (similar to 36 Wh kg(-1)), and power density (similar to 33 kW kg(-1)).